Quality Characteristics of Goshtaba Prepared by Partial Replacement of Animal Fat with Vegetable Oil: doi: 10.5958/2581-6616.2021.00004.9 - Bumla, N.A.; Wani, S.A.; Ahmad, S.R.; Sofi, A.H.; Khan, H.M.; Rehman, M.; Nabi, S.; Beigh, M.A. (Journal of Meat Science, 2022)
The current study was undertaken with an aim to optimize fat content for the development of healthier Goshtaba by replacing a of part animal fat with vegetable oil. Four treatments with a total fat content of 20% (animal and vegetable fats in different proportions) were compared among themselves for their effect on the physico-chemical, compositional, colour and sensory quality of Goshtaba. The treatments included: M0 (animal fat: vegetable fat = 20:0), M1 (animal fat: vegetable fat = 15:5), M2 (animal fat: vegetable fat = 10:10) and M3 (animal fat: vegetable fat = 5:15). The results revealed that the quality of control i.e. M0 was comparable with that of M1 as well as M2 when measured in terms of emulsion stability, cooking yield, pH, moisture, protein, fat and ash content with average value for emulsion stability as 90.43 ± 0.29 and 90.50 ± 0.36, cooking yield as 92.53 ± 0.29 and 92.76 ± 0.19, pH as 5.66 ± 0.08 and 5.43 ± 0.04, moisture as 62.30 ± 0.82 and 63.20 ± 0.65, protein as 16.15 ± 0.08 and 16.25 ± 0.10, fat as 18.14 ± 0.85 and 16.87 ± 0.60 and ash as 2.26 ± 0.19 and 2.40 ± 0.15, respectively for M0 and M2. The sensory quality of the product was improved up to M2 level; thereafter it decreased significantly for M3. The colour parameters like lightness, redness and yellowness were affected with the addition of vegetable fat. Since, the product remained in the acceptable limits up to M2, it was concluded that 50% of animal fat can be replaced with vegetable fat without affecting the quality of Goshtaba.